Educar para a informação: a importância de formar professores em educação midiática e no combate à desinformação - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
In the current scenario of extreme polarization, "Fake News", disinformation and misinformation are proliferating, phenomena intensified by the information systems of large digital platforms. In this context, personal opinion often overrides the factuality of the news, generating a paradox in which expanded freedom of expression is confronted with the need to delineate its limits. The research in question problematizes how to train teachers to mediate teaching and learning processes, guided by the context of Media Education, that understand, identify and combat disinformation. The aim of this thesis is to discuss an approach to initial teacher training in Media Education, implementing and analyzing pedagogical practices that incorporate strategies to combat disinformation, with students on degree courses at the Federal University of Western Pará - UFOPA. As the research is guided by the development of practical solutions, the methodological approach proposed is Design Based Research - DBR, which is a method based on the epistemology of Design Science and Design Science Research, also aligned with the Theory of Psychological Inoculation as a possible path for this implementation. The results of the research pointed to the lack of knowledge of teachers in initial training about the concept of Media Education, but when these future teachers come to understand it, they become able and willing to incorporate it into their teaching practices. In addition, we consider it feasible to implement Media Education from a transversal perspective, confirming that teachers have difficulties in identifying true and false information, due to the complexity of the phenomenon of disinformation and that the use of digital games, based on the Inoculation Theory, contributes to teachers understanding the main approaches to psychological persuasion, developing psychological "immunity" against on line disinformation.
Keywords: Educação Midiática; Formação de Professores; Desinformação; CNPQ::CIÊNCIAS HUMANAS; Educação na Amazônia: formação do educador, práxis pedagógica e currículo